Actinomyces graevenitzii Pulmonary Abscess Mimicking Tuberculosis in a Healthy Young Man - Smaranda Gliga; Mathilde Devaux; Marine Gosset Woimant; Dominique Mompoint; Christian Perronne; Benjamin Davido (Canadian Respiratory Journal)
Pulmonary actinomycosis is a rare disease that is often misdiag-nosed as tuberculosis or lung cancer. Actinomyces graevenitzii is a relatively new recognized Actinomyces species isolated from various clinical samples. The authors report a case of pulmonary actinomycosis caused by A graevenitzii. A computed tomography examination revealed an excavated consolidation in the middle right lobe of a previously healthy young man who presented with a long history of moderate cough. Cultures of the bronchoalveolar lavage fluid confirmed the diagnosis of pulmonary abscess caused by A gravenitzii. At the three-month follow-up consultation and, after six weeks of high-dose amoxicillin, the pulmonary lesion had completely disappeared.